THU0181 Clinical characteristics of rheumatoid arthritis patients ongoing methotrexate therapy not achieving DAS28 "low diseases activity": a matched case-control analysis from the mari study. (15th June 2017) - Giusti, A; Manara, M; Bruschi, E; Azzolini, V; Beyene, N Belai; Corbanese, S; Gennaro, F De; Martin-Martin, LS; Colella, AB Molica; Pozzi, MR; Romeo, N; Rossini, T; et al.
Abstract : Background: Methotrexate (MTX) is the DMARD of first choice in the treatment of rheumatoid arthritis (RA). Objectives: To investigate the clinical characteristics and describe therapeutic approaches in RA patients ongoing MTX not achieving a DAS28 "low disease activity" score. Methods: This is a case-control analysis including 186 patients (mean age±SD, 61±12 years, 16% males) who did not achieve a DAS28 "low disease activity" score (defined by a value ≤3.2) and 558 age- and gender-frequency-matched (1:3), randomly selected controls (mean age age±SD, 61±13 years) who achieved a DAS28 "low disease activity" from the original cohort investigated in the MARI study. The MARI study enrolled RA patients on treatment for at least 12-month with MTX. Demographic, clinical, laboratory and pharmacological characteristics of patients recorded at baseline visit were considered for the current analysis. We first compared the characteristics of patients who reached the endpoint with those of subjects who did not by univariate analyses, thereafter, we performed a multivariate model to identify predictors of not achieving the endpoint. We further investigated the therapeutic approaches in patients not achieving the endpoint. Results: Compared to patients with a DAS28 ≤3.2, subjects not achieving the endpoint presented with a significant higher (mean±SD) weight and BMI (DAS28 ≤3.2: 25±4 versus DAS28 >3.2: 26±5, P=.022), and longer duration of symptoms (months±SD) before the RA diagnosis (11±15 versus 15±20, P=.009). A higher proportion of subjects within the group not achieving the endpoint presented with polyarticular disease (DAS28 ≤3.2: 57% versus DAS28 >3.2: 96%, P<.001), erosive arthritis (49% versus 73%, P<.001), extra-articular symptoms (3% versus 10%, P<.001), positive RF test (63% versus 73%, P=.013), and increased CRP (13% versus 53%, P<.001). The proportion of patients treated with oral MTX was 25% in the subgroup with DAS28 ≤3.2 and 15% in the subgroup with DAS28 >3.2 (P=.004). In the logistic regression analysis, the variables predictive of a DAS28 >3.2 were polyarticular disease (OR 4.0, 95% CI 2.4–6.7, P<.001), erosive arthritis (OR 2.2, 95% CI 1.4–3.4, P<.001), and increased CRP (OR 7.4, 95% CI 4.9–11.4, P<.001). In patients who did not reach the endpoint, the main therapeutic strategies were: a change in the route of administration of MTX (DAS28 >3.2: 13% versus DAS28 ≤3.2: 4%, P<.001) in favor of subcutaneous MTX, an increase of the dose of MTX (13% versus 2%, P<.001), and the prescription of a new biologic (12% versus 1%, P<.001). Conclusions: Our results identified a number of variables potentially associated the risk of not achieving a DAS28 "low disease activity" score in RA patients ongoing MTX treatment. Longitudinal studies are warranted. Disclosure of Interest: None declared